PENGGUNAAN METODE DRILL UNTUK MENINGKATKAN PERMAINAN ALAT MUSIK REBANA DI SMA - Danu Ardy Sulistyo; Nurmila Sari Djau; Asfar Muniir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research was motivated by the problems which was faced by the students of class XI at Taruna Bumi Khatulistiwa High School where there were still many of them had lack of skills in playing a tambourine. The purpose of this research was to describe the improvisation of the students of class XI Social I at Taruna Bumi Khatulistiwa High School skills in playing a tambourine by using a drill method. The first finding in the first cycle were the students still showed unsatisfied results in playing a tambourine where the students' poses when playing a tambourine were still improper and the sounds produced while they were playing a tambourine was worse as well as the technique used by the students were still worse when playing it. On the other hand, in the second cycle, the finding showed that the students' poses when playing a tambourine was proper and the aspects of the sound produced when they were playing a tambourine were better than before.. Finally, from the findings above, it can be concluded that the students of class XI Social I at Taruna Bumi Khatulistiwa High School skills in playing a tambourine improved by using a drill method.Keywords: Drill Method and Tambourine